Pemberian ASI eksklusif berdasarkan faktor internal ibu di Desa Sri Kuncoro Kabupaten Bengkulu Tengah - Bintang Agustina Pratiwi; Junita Junita; Emi Kosvianti; Oktarianita Oktarianita (MEDIA ILMU KESEHATAN, 2022)
Background: There are 775 babies exclusively breastfed from 1,150 babies. Mother is the main character in exclusive breastfeeding. To find out the internal maternal factors associated with exclusive breastfeeding. Objective: To determine the internal maternal factors associated with exclusive breastfeeding. Method: Quantitative with cross-sectional research. November–December 2021 was the Sri Kuncoro Health Center's operating area for the analysis. Just 97 moms were included and excluded from the study's 109 total samples. This study's dependent variable is exclusive breastfeeding, and the independent factors include age, education, employment, number of children, and mother knowledge. Data were acquired using valid and reliable questionnaires and analyzed using univariate and bivariate phases.Results: As many as 63.9 per cent of mothers who provide exclusive breastfeeding, 84.5 per cent aged 20-35 years, work in the informal sector 71.1 per cent, have low education 55.7 per cent, number of children ≤ 2 children and have poor knowledge 54.6 per cent. There is a relationship between work, education and knowledge of mothers and exclusive breastfeeding (p-value < 0.05) Conclusion: Mothers will exclusively breastfeed their children if they work in the informal sector, have higher education and are well-rounded